2014
DOI: 10.4095/293788
|View full text |Cite
|
Sign up to set email alerts
|

Variability of coastal change along the western Yukon coast

Abstract: Because the Yukon coast along the Beaufort Sea has the highest ground ice contents in the Canadian Arctic and, in addition, faces the direction of most effective storms, this section of coast is considered to be highly vulnerable to the effects of climate change. In order to gain insight into the regional coastal dynamics, a quantification of coastal change was undertaken that allowed the determination of spatial and temporal variability of coastal change along a 35 km long section of coast, stretching from Ko… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 50 publications
0
15
0
Order By: Relevance
“…Ground ice volumes of up to 66% (Couture, ) between Komakuk Beach and the Canada‐U.S. American border result in thermo‐abrasion and thermo‐denudation processes that alter the landscape, for example, by active layer detachments, or block failures (Konopczak et al, ). The river deltas of the Malcom and Firth River are fronted by a 30.5‐km‐long system of barrier spits and barrier islands termed Nunaluk Spit, which protects the delta coast (Figure ).…”
Section: Study Areamentioning
confidence: 99%
See 1 more Smart Citation
“…Ground ice volumes of up to 66% (Couture, ) between Komakuk Beach and the Canada‐U.S. American border result in thermo‐abrasion and thermo‐denudation processes that alter the landscape, for example, by active layer detachments, or block failures (Konopczak et al, ). The river deltas of the Malcom and Firth River are fronted by a 30.5‐km‐long system of barrier spits and barrier islands termed Nunaluk Spit, which protects the delta coast (Figure ).…”
Section: Study Areamentioning
confidence: 99%
“…The only study systematically investigating the whole Yukon coast by means of aerial imagery analyses from the 1950s and 1970s was published in 1985 and reported average retreat rates of −0.5 m/a with local rates up to −5.3 m/a (Harper et al, ). Further studies have concentrated on shorter parts of the Yukon coast (Forbes, ; Konopczak et al, ; Lantuit & Pollard, ; McDonald & Lewis, ; Radosavljevic et al, ) or on much shorter timescales (Obu et al, ). These studies reported mean shoreline change rates of −0.45 to −3.0 m/a, which corresponds well with shoreline change rates published by Harper et al ().…”
Section: Introductionmentioning
confidence: 99%
“…Journal of Geophysical Research: Earth Surface 10.1002/2017JF004231 is a general spatial pattern of decreasing erosion rates from west to east along the Yukon Coast [Konopczak et al, 2014].…”
Section: Introductionmentioning
confidence: 99%
“…Many cultural sites along the mainland coast, as well as on Qikiqtaruk (Herschel Island), have been or are about to be eroded (Jones et al 2008;Friesen 2015;Radosavljevic et al 2016;O'Rourke 2017). Investigations of the DEW line site at Qamaqaaq (Komakuk Beach) show that the landing strip has been eroding, on average, by approximately 1 m/a since the 1950s (Solomon 1998;Konopczak et al 2014).…”
Section: Introductionmentioning
confidence: 99%